(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
On the basis of new projects in the regions, great attention is being paid to improving the infrastructure of the city, providing clean drinking water, paving internal roads. All resources and efforts are being mobilized to ensure that every person lives happily.